Are There Differences in Elite Youth Soccer Player Work Rate Profiles in Congested vs. Regular Match Schedules?. Issue 2 (February 2021) - Zanetti, Vinicius; Carling, Christopher; Aoki, Marcelo S.; Bradley, Paul S.; Moreira, Alexandre
Abstract : Abstract: Zanetti, V, Carling, C, Aoki, MS, Bradley, PS, and Moreira, A. Are there differences in elite youth soccer player work rate profiles in congested vs. regular match schedules? J Strength Cond Res 35(2): 473–480, 2021—Official international tournaments in which youth soccer players participate can involve very congested schedules. Yet, no information regarding physical and technical match performance during congested vs. regular (noncongested) cycles is available. In this study, accelerations, decelerations, mean metabolic power (MP), and technical performance (offensive and defensive variables) were compared across very congested match (VCM; 10 international matches played over 3 successive days, including 2 days with 2 consecutive matches separated by a 4- to 5-hour interval) and 10 regular (noncongested match [NCM]) match periods in elite male Under 15 (U15, n = 11) and Under 17 (U17, n = 13) soccer players. Players wore a 15-Hz Global Positioning System unit with a 100-Hz triaxial accelerometer. The session rating of perceived exertion (RPE) were assessed 30 minutes after match. Results showed a higher number of accelerations per minute observed in VCM vs. NCM (U15; 2.27 ± 0.35 vs. 2.12 ± 0.23; effect size [ES] = 0.49; U17; 2.27 ± 0.41 vs. 2.01 ± 0.31; ES = 0.69). Decelerations per minute were higher during VCM (U15; 1.99 ± 0.27 vs. 1.84 ± 0.25; ES = 0.55; and U17; 1.98 ± 0.35 vs. 1.80 ± 0.27; ES = 0.56). Mean MP was higher in the VCM (U15; 0.42 ± 0.06 vs. 0.37 ± 0.02; ES = 1.08; U17; 0.46 ± 0.03 vs. 0.30 ± 0.03; ES = 1.94). Technical actions per minute were higher in the VCM for U17 (ES = 1.60 and 1.37, for offensive and defensive performance, respectively) but lower (during VCM) for U15 (ES = 3.59 and 0.28, for offensive and defensive performance). U15 reported a higher session RPE in the VCM (7.9 ± 0.5 AUs vs. 6.9 ± 0.5 AUs). The findings suggest that running activity in these youth players was unaffected overall in tournaments with congested schedules, and that the intensity of match-play was actually greater than in regular match schedules.